Development of control and chipping skills test instruments: u-23 professional futsal players in Central Java province - andri arif kustiawan; Pomo Warih Adi; Bimo Alexander; Agus Pribadi; Danang Ari Santoso; Yayan Wardiyanto; Guntur Sulistyo Ariwibowo; Ali Munir (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Introduction: The measurement of basic skills in playing futsal requires the right instruments so that the level of futsal skills can be measured for the purposes of learning and improving achievement.